A morte na poesia de Jorge Wanderley: lírica e formas autobiográficas - Nascimento, Jorcilene Alves do (2018)
Jorge Wanderley is a forgotten name among the poets of the 1960s and 1990s. He is remembered only for translations, critical texts and his career as Literature professor. However, he, who was born in Pernambuco, Brazil, had more than seven poetic books published and a posthumous anthology organized by his wife, Márcia Wanderley. Despite consistent poetic production, his poems received only brief critical readings, which points to the lack of a deeper analysis. Therefore, this reasearch aims to offer an in-depth reading of the poet’s work. A recurrent theme was noticed in Wanderley’s lyrical production: death. It becomes even more peculiar in the poet's biography. Just like Manuel Bandeira, Wanderley knew very early that he had a serious heart problem and lived with it until his second and last heart attack in 1999. The research showed that it is possible to associate the death theme in his poetry to his heart condition. Besides other biographical data, Wanderley’s poetry confirms this theme in autobiographical forms. In his work, epitaphs, wills and inventories were found and selected as a corpus for this research. The proposal was to analyse autobiographical issues in his lyrical work using formal appropriations related to death in Wanderley's poetry to understand how the ambiguous autobiographical data make up a fictionalization of his lyrical self. To a certain extent, this research brings the empirical self closer to the lyrical self in the selected poems. This work was based on the studies on autobiography in poetry, mainly of Dominique Combe (2009) and Paul De Man (2012). This was done in order to understand the presence of these two elements in the texts, by considering the autobiographical aspect of the poetry as a possible reading that does not exclude the author but maintains an ambiguous relationship and threshold between fiction and reality. In this sense, the purpose of this dissertation is to analyze how such poetic forms build the representation of the lyrical self and which meanings death assumes according to the existing theories on autobiography and poetry.